PENGARUH ENVIRONMENTAL, SOCIAL & GOVERNANCE TERHADAP FIRM VALUE PADA PERUSAHAAN INDEKS ESG BURSA EFEK INDONESIA PERIODE 2020-2023 - Carsen, Maximillon (Jurnal Akuntansi Pajak dan Manajemen (TAJAM), 2024)
This research aims to examine the influence of Environmental, Social & Governance (ESG) on Firm Value. This research design an associative design, secondary data from the annual reports, financial reports, ESG scores, and share prices of listed companies studied, This sample research are listed companies included in the ESG ranking of the Indonesia Stock Exchange for 2020-2023 period. This result found that ESG has a negative effect on firm value